2014
DOI: 10.1002/cbf.3084
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin a modulates intracellular reactive oxygen species through SOD2 and FOXO1 in human bone marrow‐mesenchymal stem cells

Abstract: Engraft cells are often exposed to oxidative stress and inflammation; therefore, any factor that can provide the stem cells resistance to these stresses may yield better efficacy in stem cell therapy. Studies indicate that histone deacetylase (HDACs) inhibitors alleviate damage induced by oxidative stress. In this study, we investigated whether regulation of reactive oxygen species (ROS) occurs through the HDAC inhibitor trichostatin A (TSA) in human bone marrow-mesenchymal stem cells (hBM-MSCs). Intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Antioxidant enzymes such as SOD1, SOD2, and catalase are known as major scavengers of iROS (Johnson & Giulivi 2005 ). Expression of these enzymes is decreased in cells exposed to excessive oxidative stress, resulting in the accumulation of iROS (Huang & Tindall 2007 ; Jeong & Cho 2015b ). Since we have shown that UP-Ex pretreatment protects against oxidative stress in hBM-MSCs, it is reasonable to assume that this protection is due to moderated iROS levels.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes such as SOD1, SOD2, and catalase are known as major scavengers of iROS (Johnson & Giulivi 2005 ). Expression of these enzymes is decreased in cells exposed to excessive oxidative stress, resulting in the accumulation of iROS (Huang & Tindall 2007 ; Jeong & Cho 2015b ). Since we have shown that UP-Ex pretreatment protects against oxidative stress in hBM-MSCs, it is reasonable to assume that this protection is due to moderated iROS levels.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC inhibition reduced the production of ROS in cardiomyoblasts exposed to hypoxia/reoxygenation [ 29 ]. Recently, it was also shown that the intracellular increase of ROS levels following exposure to hydrogen peroxide was suppressed by TSA [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, multiple end points for HDAC-inhibitor activity have been reported, including gene expression, cell-cycle arrest, cell differentiation, antiangiogenesis, cell death, and autophagy. 81 In addition, HDAC inhibitors have been reported to generate ROS and modulate redox levels in cells, [82][83][84][85][86][87] resulting in DNA damage and activation of the DDR. 88,89 Others have shown that key DNA-repair molecules including Ku70/Ku80, DNA-PK, RAD50, RAD51, BRCA1/2, and MRE11 are downregulated by vorinostat and other HDAC inhibitors in combination with radiotherapy, leading to RIF persistence.…”
Section: Chromatin Structure and Targetingmentioning
confidence: 99%